Evaluation of the effectiveness of release myofascial treatment in the patello-femoral syndrome - Srokowska, Anna Maria; Lewandowski, Andrzej; Balmas, Paweł; Kurczewski, Mikołaj; Srokowski, Grzegorz; Siedlaczek, Marcin (Journal of Education, Health and Sport, 2018)
Introduction: Patello-femoral syndrome is one of the common syndromesoverload knees. The most common symptom reported by patients is severe pain during activities such as climbing stairs or running. The main cause of this syndrome is ataxia knee. This is caused by imbalance, the voltage of fascial structures immediately surrounding the pond, as well as the structures remote. Used treatment is a surgical procedure involving the plasticity retinacula patella or conservative treatment in the form of physiotherapy. Untreated disease lead to degeneration of cartilage and other damage to the knee.Goals: The aim of the study is to determine the efficacy of therapy in the form myofascial release in the patello-femoral pain . It is hypothesized that the treatment carried out effectively and permanently eliminates the problem of patello-femoral syndrome, while reducing or completely removing the associated symptoms.Material and Methods: The study included a group of 23 men and womenranging in age from 15 to 57. The study was conducted in which established acts provoking symptoms, patients assessed the severity of pain arising in the activities of everyday life. Before and after the therapy was performed diagnostic tests confirming the presence of excessive lateral pressure syndrome.Results: Statistical tests before and after treatment were used for statistical evaluation of differences in the obtained results.After the treatment, the pain completely disappeared and crepitations in the joints are reduced or gone. The change has been a tension retinacula patella, reducing the lateral patellar compression.Conclusions: The myofascial release as a form of conservative treatment ofsymptoms associated with lateral patellar syndrom, effectively and permanently reduces or eliminates the problems associated with this disease, and thus is an effective treatment.